A history of violence [videorecording (DVD)] - Cronenberg, David, 1943-; Mortensen, Viggo, 1958-; Bello, Maria, 1967-; Harris, Ed, 1950-; Hurt, William (New Line Home Entertainment : Distributed by Warner Home Video, 2006)
Tom is a loving, well-respected family man from a small Indiana town. When two criminals show up at his diner, Tom is forced to take action and thwart the robbery attempt. Suddenly heralded as a local hero who took the courage to stand up to crime, people look up to Tom as a man of high moral regard. But all the media attention attracts the likes of the mob, who show up at Tom's doorstep. Is it a case of mistaken identity or does Tom have a history that no one knows about?